Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Kemampuan Menulis Teks Ekplanasi Siswa Kelas VIII SMPS Muhammadiyah 1 Medan - Della Amadiah; Atika Wasilah (Pusat riset dan Inovasi Nasional, 2025)
The main objectives of this study were to determine whether students of grade VIII of SMPS Muhammadiyah 1 Medan could write explanatory texts using the Inquiry model, to find out whether they could write explanatory texts using the Teams Games Tournament model, and to find out how the Teams Games Tournament model affected the ability of grade VIII students in writing explanatory texts. A total of 64 students were selected from a population of 351 grade VIII students and divided into two groups: the experimental group (32 participants) and the control group (32 participants). General statements, sequences of events, conclusions, causal and chronological conjunctions, technical terminology, and nouns were some of the instruments used. After the quantitative test of the two experimental groups, data analysis techniques such as hypothesis testing, normality testing, and analysis requirements testing were applied. The calculated t value > t table (3.42423 > 2.04227), which shows that grade VIII students at SMPS Muhammadiyah 1 Medan significantly increased their capacity in writing explanatory texts during the 2023/2024 academic year, indicating that the Teams Games Tournament Model has a significant impact on the ability to write explanatory texts.